2020
DOI: 10.1002/rcm.8778
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical mass spectrometry: Ab initio study of b2‐ion formation mechanisms for the singly protonated Gln‐His‐Ser tripeptide

Abstract: Rationale: Both amide bond protonation triggering peptide fragmentations and the controversial b 2 -ion structures have been subjects of intense research. The involvement of histidine (H), with its imidazole side chain that induces specific dissociation patterns involving inter-side-chain (ISC) interactions, in b 2 -ion formation was investigated, focusing on the QHS model tripeptide. Methods:To identify the effect of histidine on fragmentations issued from ISC interactions, QHS was selected for a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
(181 reference statements)
0
2
0
Order By: Relevance
“…This aspect has been recently discussed based on MS 3 experiments coupled with quantum chemical calculations, which suggest the coexistence of oxazolone and lactam for the singly protonated Gln-His-Ser tripeptide, the DKP being disfavored by an additional reaction step. 53 The fragmentation mechanism of protonated DKP dipeptides isolated in an ion trap has been questioned too. The CID of protonated model DKPs like cyclo Gly-Gly, cyclo Ala-Ala, or cyclo Ala-Gly, 52,54 has been widely debated, based on the experimental evidence that protonated cyclo Ala-Ala loses CO and CO+NH 3 , while protonated cyclo Gly-Gly loses 2 CO at higher energy.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect has been recently discussed based on MS 3 experiments coupled with quantum chemical calculations, which suggest the coexistence of oxazolone and lactam for the singly protonated Gln-His-Ser tripeptide, the DKP being disfavored by an additional reaction step. 53 The fragmentation mechanism of protonated DKP dipeptides isolated in an ion trap has been questioned too. The CID of protonated model DKPs like cyclo Gly-Gly, cyclo Ala-Ala, or cyclo Ala-Gly, 52,54 has been widely debated, based on the experimental evidence that protonated cyclo Ala-Ala loses CO and CO+NH 3 , while protonated cyclo Gly-Gly loses 2 CO at higher energy.…”
Section: Introductionmentioning
confidence: 99%
“…52 In contrast to peptides containing aliphatic residues, peptides containing histidine show diketopiperazine or lactam in addition to oxazolone fragments. 51,53,54 We recently showed that the CID of cyclo (Phe-His)H + shows a very high sensitivity of CO loss efficiency to the chirality of the residues, due to the proton shuttling mechanism from the imidazole substituent to the amide. 45 We determine here the structure of the protonated dimer of cyclo (LPhe-LHis) and cyclo (LPhe-DHis), noted in short (c-LL) 2 H + and (c-LD) 2 H + , in a room-temperature ion trap, by Infra-Red Multiple Photons Dissociation (IRMPD) and compare them to quantum chemical calculations in the frame of the density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%